Does lacking a car put the brakes on activity participation? Private vehicle access and access to opportunities among low-income adults. (June 2020) - Morris, Eric A.; Blumenberg, Evelyn; Guerra, Erick
Abstract: Private vehicle travel entails costs to society. However, in a world designed around the automobile, adults who lack access to a vehicle for economic reasons may experience a significant handicap due to constrained mobility and accessibility. This paper examines whether private vehicle access is associated with the quantity and quality of out-of-home activities in which low-income individuals participate. We use pooled data from multiple time use surveys drawn from the Netherlands, Canada, Spain, and the United Kingdom, and employ Cragg two-part hurdle modeling to determine whether there is an association between household vehicle access and participation in twelve out-of-home activity types. As a robustness check, we also estimate multiple discrete continuous extreme value (MDCEV) models. Further, we examine travel time by mode for those with and without vehicles. Finally, we use American Time Use Survey data and fixed-effects panel models to determine the subjective well-being that is associated with our out-of-home activity types. A lack of private vehicle access is associated with significantly less frequent out-of-home activity participation, both in the aggregate and for seven of the twelve individual activities. Moreover, the activities most likely to be foregone are generally associated with high subjective well-being, suggesting that constrained mobility comes with significant emotional costs. We find a greater "activity penalty" for rural residents and for Canadian residents without vehicle access; urbanites without vehicles in the U.K. are the only geographic group which do not exhibit an activity penalty. Finally, respondents with vehicle access spend more total time traveling, although those without private vehicles partially offset spending less time in them with higher use of alternative modes. Overall, the findings suggest that the lack of a private vehicle is deleterious for quality of life, raising troubling questions about inequity possibly arising when people are denied access to vehicles for economic reasons.